Risk factors for "late-to-test" HIV diagnosis in Riverside County, California. Issue 39 (September 2016) - Gardner, Aaron T.; Napier, Rachaline; Brown, Brandon
Abstract : Abstract: Patients diagnosed late in the course of HIV infection are at an increased risk of negative health outcomes and are more likely to transmit HIV to others. Using the CDC's definition for AIDS, we analyzed case report data from persons diagnosed with AIDS within 12 months of an HIV diagnosis ("late-to-test") in Riverside County, CA, between 2009 and 2014. Of 1385 HIV cases, 422 (30.5%) were late-to-test. Factors associated with late-to-test were: having no insurance ( P = 0.005), being Hispanic ( P = 0.002) and being between 45 and 64 years of age ( P < 0.001). Females ( P = 0.013) and those in the eastern region of Riverside County ( P = 0.002) were less likely to be late-to-test. In the absence of universal HIV testing, interventions to decrease late testing are needed.